A Study on the Histopathological Changes in Cases of Pesticide Poisoning and Proposed Diagnostic Algorithm - Swapan K. Adhikari; Soumeek Chowdhuri; Parthapratim Mukhopadhyay (Indian Journal of Forensic Medicine & Toxicology, 2021)
Pesticide poisoning in developing world is a global public health problem. Incidences of poisoning areincreasing with socio-economic hurdles. Often reporting and chemical examination of samples collectedfrom viscera are difficult to precisely diagnose cases and therefore extensive studies on histopathologicalcorroborations of vital organs such as stomach, liver and kidney is necessary along with socio-demographicdata. The common autopsy findings were cyanosis in the lips, in the fingertips and nose. Histologicalfindings in stomach revealed congestion, erosion of muscularis mucosa, submucosal petechial haemorrhagesand necrosis. Liver shows congestion, sinusoidal dilution, degeneration of hepatocytes and haemorrhages.Kidney shows tubular necrosis and glomerular congestion. However, history of poisoning along withautopsy and histological findings are considered as strong evidence for acute organophosphorous poisoning